DISCOLORATION OF HEAT CURED ACRYLIC RESIN PLATE DUE TO INFUSION OF TELANG FLOWER TEA (Clitori ternatea) - Safira Isnaeni, Rheni; Yulia Dewi, Zwista; Shodiqin Pratama Putra Nugraha, Muhammad (Journal of Health and Dental Sciences, 2025)
Tooth loss is a common oral health problem that can lead to reduced masticatory function, compromised aesthetics, and impaired speech. Heat-cured acrylic resin is a widely used denture base material due to its favorable aesthetics, ease of manipulation, affordability, and non-toxicity. However, its color stability can be compromised by dietary exposure to pigmented substances such as coffee, tea, and fruit juices. Herbal beverages, including telang flower (Clitoria ternatea) tea, are increasingly consumed in Indonesia. This study aimed to determine the effect of telang flower tea infusion on the color stability of heat-cured acrylic resin over varying immersion durations.This experimental study used a pre-test and post-test control group design. Heat-cured acrylic resin plate samples were immersed in telang flower tea infusion for 1, 3, 5, and 7 days. Color changes were measured using a spectrophotometer at a wavelength of 680 nm. Data were analyzed using one-way ANOVA to assess differences in color change across groups, followed by a post hoc Tukey test. (P<0.05). Results revealed significant differences in color changes between the control and treatment groups (p=0.02), with the greatest discoloration observed after 7 days of immersion. The degree of color change increased with longer soaking durations, indicating a time-dependent effect of telang flower tea on the acrylic resin surface. Conclusion are telang flower tea infusion significantly affects the color stability of heat-cured acrylic resin. The longer the immersion time, the greater the discoloration observed. These findings suggest that dietary habits involving herbal teas may influence the aesthetic durability of denture materials. DOI : 10.54052/jhds.v5n1.p43-50